2010
DOI: 10.1007/s11096-010-9451-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost reduction associated with restriction policy on dispensing intravenous esomeprazole in lebanon

Abstract: Even though the clinical role of pharmacy practice in Middle Eastern countries is limited, this study highlighted the impact of the pharmacist on cost through the implementation of restriction policy during dispensing procedure, leading to a cost reduction by four folds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…There is significant statistical difference between IVPPIs and oral PPIs cost, the IVPPIs calculated cost was 20$ per ampule, which includes the cost of the IV vial, 100 mg solution bag, 5ml syringe IV line, angiocath, and local anesthetic cream in comparison to oral PPI price which was 3 $ per capsule [30]. This also confirmed in the questioner results of this study (Appendix II).…”
Section: Rq7supporting
confidence: 83%
See 2 more Smart Citations
“…There is significant statistical difference between IVPPIs and oral PPIs cost, the IVPPIs calculated cost was 20$ per ampule, which includes the cost of the IV vial, 100 mg solution bag, 5ml syringe IV line, angiocath, and local anesthetic cream in comparison to oral PPI price which was 3 $ per capsule [30]. This also confirmed in the questioner results of this study (Appendix II).…”
Section: Rq7supporting
confidence: 83%
“…RQ4: which route is more time consuming (nurses interview) the IV route is more time consuming for both nurse and patient than the oral route which needs less time as mentioned in previous studies and seen in the results of the questioner ( Appendix II) [32] RQ5: Is it possible to reduce the costs if we applied oral route when possible instead of parenteral route? (Interview with the responsible pharmacists confirmed that, knowing the big price difference between the IV and oral route) [30].…”
Section: Rq2mentioning
confidence: 96%
See 1 more Smart Citation
“…Interventions were in following areas antimicrobial management [17][18][19][20][21][22], targeted drug programmes [23][24][25][26], multidimensional clinical pharmacy service [27][28][29], paediatric programmes [30,31], renal specialist [32,33], pharmacotherapeutic optimisation [34,35], intensive care service [36,37] and neurosurgery [38]. All intervention types have been identified in previous reviews of the literature [10][11][12][13].…”
Section: Clinical Pharmacy Interventionsmentioning
confidence: 99%
“…Pharmacists discontinued unnecessary vitamin D supplements over a 1 year period, resulting in cost savings of US$111,282.40 [24]. A group of hospital pharmacists reviewed the appropriateness of prescribing iv esomeprazole resulting in savings of US$21,233 per month [25]. Pharmacists in Taiwan reviewing the appropriateness of activated protein C therapy in septic patients over a 2 year period, demonstrated a reduction in total direct medical costs [26].…”
Section: Targeted Drug Programmesmentioning
confidence: 99%